The Effectiveness of Stop Motion Video Assisted Discovery Learning Model on Mathematics Problem Solving Ability in Elementary School Students - Noviani Try Ardhiati; Kartono Kartono; Rochamd Rochmad (Educational Management, 2021)
The purpose of this study was to determine the effectiveness of the Stop Motion Video Assisted Discovery Learning model on mathematical problem solving abilities. The research method used in this study is a quasi-experimental quantitative method with nonequivalent control group design. The population in this study was the Prince Diponegoro cluster, Pecalungan District, Batang Regency. Sampling was done by using simple random sampling. The data collection technique used a mathematical problem solving ability test, observation, and documentation. This study was analyzed using t-test. The results showed that (1) the ability to solve mathematical problems with the effectiveness of the Video Stop Motion Assisted Discovery Learning model had reached 75% classical completeness, (2) the average mathematical problem solving ability with the effectiveness of the Video Stop Motion Assisted Discovery Learning model was better than average. -flat. students' mathematical problem solving abilities using the expository learning model, (3) the proportion of students' mathematical problem solving abilities using the effectiveness of the Stop Motion Video Assisted Discovery Learning model is greater than the proportion of students' mathematical problem solving abilities using the expository learning model.